Learning Appreciation of Abstract Painting to Improve Creativity in Visual Communication Design Student at SMKN 14 Bandung - Bela Pertiwi, Annisa; Astuti, Marisa; Reka Prasetya, Arus (International Journal of Psychosocial Rehabilitation, 2020)
This research was conducted in an effort to increase the imagination, creativity, and student learning outcomes of Visual Communication Design programs at SMKN 14 Bandung through appreciation of abstract painting. From appreciation of abstract painting activities, students are expected to be able to obtain aesthetic experience from their needs to fulfill the sense of beauty, develop the ability to visualize, and also be useful to facilitate the process of students' art work in learning Visual Communication Design. The study in this research uses classroom action methods, which are carried out through a quantitative approach. In this research, there is an analysis of students 'perceptions of abstract paintings to show students' knowledge and responses about abstract painting. In addition, there is an analysis of psychomotor abilities in the form of the practice of abstract painting to measure aesthetic experiences and the results of students' perceptions when appreciating abstract paintings, resulting in an urge to create abstract paintings.